Vilfredo Pareto. History, his history - Toscano, Mario (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2018)
Pareto biographical and intellectual experience offers a privileged point of view on First World War. His life work, Treatise on General Sociology, was published in 1916 by Barbera Publisher in Florence. It is through the conceptual tools contained in this work that he deciphers the ongoing conflict. His interpretative method is based on the distinction between residues and derivations. The firsts are the real motifs that determinate actions, the seconds are false explanations men create to justify their behaviour. War is a conflict between residues and more specifically between two residues: the persistence of aggregates – a conservative residue, politically represented by Germans and Central Powers – and the instinct for combinations – typical of innovators, represented by the Allies. Post war disorder cannot last and be tolerated by any stable social system. Pareto in a first moment is sceptical toward Fascism but he was fascinated by Mussolini’s personality later, when he recognises him as the only man capable to re-establish social order in a country out of control. Pareto’s support to Fascism is ultimately a support to a realistic principle able to use Machiavelli methods to beat all fractions that without a political synthesis can threat the social life of a country.